2011
DOI: 10.1186/1476-511x-10-198
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, mastocytosis, and diminished adipocytokine gene expression accompany reduced epididymal fat mass in long-standing diet-induced obese mice

Abstract: BackgroundObesity is characterized by increased cell death and inflammatory reactions in the adipose tissue. Here, we explored pathophysiological alterations taking place in the adipose tissue in long-standing obesity. In the epididymal fat of C57BL/6 mice fed a high-fat diet for 20 weeks, the prevalence and distribution of dead adipocytes (crown-like structures), mast cells (toluidine blue, mMCP6), macrophages (F4/80), and apoptotic cells (cleaved caspase-3) were measured. Moreover, gene and/or protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 38 publications
(56 reference statements)
2
43
1
2
Order By: Relevance
“…Another consideration is that in the current study, epididymal fat samples were taken from random regions of this visceral fat depot. A study published subsequently revealed that epididymal adipose tissue may not have uniform metabolic activity across its proximal and distal (relative to the testes) segments (Altintas et al, 2011), which may explain the variability of gene expression in our samples. Given these concerns, it is likely that the present study was not sufficiently powered to detect significant differences in adipokine gene expression.…”
Section: Discussionmentioning
confidence: 90%
“…Another consideration is that in the current study, epididymal fat samples were taken from random regions of this visceral fat depot. A study published subsequently revealed that epididymal adipose tissue may not have uniform metabolic activity across its proximal and distal (relative to the testes) segments (Altintas et al, 2011), which may explain the variability of gene expression in our samples. Given these concerns, it is likely that the present study was not sufficiently powered to detect significant differences in adipokine gene expression.…”
Section: Discussionmentioning
confidence: 90%
“…It was previously described that the AT of lean and obese mice differ substantially with regards to mast cell numbers (14, 29, 30). In addition, the obesity-related increase of mast cell numbers is more prominent in gAT (29), thereby suggesting that mast cells might participate in obesity-related AT inflammation and metabolic dysregulation (12).…”
Section: Discussionmentioning
confidence: 99%
“…This white adipose tissue deposit contained an abundance of mast cells and macro phages, and the protein levels of both mMCP-6 and the macrophage marker F4/80 were increased, as were the gene-expression levels of TNF and IL-10. 132 Inasmuch as mast cells in the white adipose tissue of mice release TNF, neutralization of TNF ameliorates insulin resistance in various rodent models, 133 and obese mice lacking TNF have improved insulin sensitivity. 134 Adipogenic factors increased the expression of adipocyte biomarkers from a stromal vascular fraction prepared from Kit W-sh/W-sh mice, whereas mast-cell reconstitution in Kit W-sh/W-sh mice reduced the expression of preadipocyte biomarkers in white adipose tissue from these recipient mice, indicating that mastcell-deficiency led to the accumulation of pre-adipocytes in white adipose tissue (Figure 7).…”
Section: Diabetesmentioning
confidence: 99%